An Academic E-government Platform for Managing Educational and Research Activities - Tsolakidis, Anastasios; Triperina, Evangelia; Chytas, Konstantinos; Triantafyllou, Ioannis; Skourlas, Christos (Journal of Integrated Information Management, 2024)
Purpose - In this article, we propose the architecture of an E- government platform for Educational and Research Management (e-EDURES) in Higher Education Institutions. An integrated strategic planning and decision support system (DSS) is included at the center of the architecture for facilitating the decisions and the design of future actions, enabled by data mining and visual analytics techniques. Design/methodology/approach - The platform study focuses on the development of services related to i) the management of educational data generated by blended learning, along with ii) the utilization of data related to R&D activities in higher education Institutions. The proposed approach studies the system architecture at four levels: data collection, data preparation, data mining, and knowledge discovery. Findings - The e-EDURES platform should be based on data mining techniques to predict the potential learning progress of each student, whereas focusing on research, Social Network Analysis, and coauthorship networks modeling using graph metrics and Data Environment Analysis have been used as a measure of the effectiveness of the research activities. Originality/value - The platform incorporates interactive visual interfaces to support Knowledge Discovery from Data Visualization, providing the user with enhanced assistance throughout the decision-making process.